Cognitive Behavioral Therapy Model of Socratic Dialogue Technique to Improve Critical Thinking Skills of Vocational High School Students - Saputra, Randi; Kurniawan, Nanda Alfan; Ralianti, Destanika Dhiffa (International Journal of Applied Counseling and Social Sciences, 2025)
The main capital for vocational high school students to apply theoretical and practical knowledge according to the needs of the world of work is critical thinking skills. Critical thinking is included in the product of psychological-dimensional activities that can be improved through guidance and counseling services. This study aims to describe the effectiveness of the cognitive behavioral therapy model of the Socratic dialogue technique to improve the critical thinking skills of vocational high school students. The approach to this research is quantitative with a quasi-experimental one group pre-test post-test method. The subjects of the study were 103 students. The sampling technique used was purposive random sampling. The data analysis technique used non-parametric statistical tests with the Wilcoxon Signed-rank test analysis method. The results of the Wilcoxon Signed rank test analysis showed a score of 0.000 <0.005, which means that the application of the cognitive behavioral therapy model of the Socratic dialogue technique is effective in improving the critical thinking skills of vocational high school students. The results of the study recommend research on gender differences in students' critical thinking skills